Validation of the DAPT score in large-scale consecutive and contemporary patients population in the real world. (17th November 2021) - Gao, Guofeng; Zhao, Yanyan; Zhang, Dong; Song, Chenxi; Song, Weihua; Feng, Lei; Zhu, Chenggang; Xu, Bo; Yin, Dong; Dou, Kefei
Abstract: Dual antiplatelet therapy (DAPT) score emerged as a tool for quantification of ischemia and bleeding risks. However, there was discrepancy of the prediction ability of DAPT score in previous studies. We aimed to assess the utility of DAPT score in a large-scale cohort of consecutive percutaneous coronary intervention (PCI) patients. This study enrolled 9, 114 patients who had undergone PCI at Fuwai Hospital in 2013, adhered to DAPT and were event-free within the first 12 months following PCI. The endpoints included primary ischemic endpoints (major adverse cardiovascular and cerebrovascular events, and myocardial infarction and/or stent thrombosis), and bleeding endpoint from 12 through 24 months after PCI. Patients were classified into low (score <2, n = 3, 989) and high (score ≥2, n = 5, 125) DAPT score groups. The incidence rates of primary ischemic endpoints and bleeding endpoint were similar between the two groups. Multivariable analysis demonstrated DAPT score not to be an independent predictor of primary ischemic endpoints or bleeding endpoint. Based on receiver operating characteristic curves analysis, the C-statistic of DAPT score for primary ischemic endpoints or bleeding endpoint did not achieve a significant extent. In this large-scale cohort of PCI patients, DAPT score did not discriminate the risks of ischemic and bleeding events.